Cylinders in Anatolia: Remarks on Early Bronze Age Seals and Sealings - M. Gökçe Dede; Umay Oğuzhanoğlu (Anadolu Araştırmaları)
Cylinder seals began to be used in Anatolia shortly after their emergence in Mesopotamia and Iran during the second half of the 4th millennium BCE. These seals, offering a wide narrative space, were used across Western Asia until the 5th century BCE. Seal impressions, which in their simplest function ensured property protection, appeared within similar timeframes. This study provides a comprehensive evaluation of cylinder seals and impressions from the 3rd millennium BCE in Anatolia, focusing on their significance during the Anatolian Early Bronze Age. Published cylinder seals and impressions are cataloged, categorized by region and period, and analyzed. The findings revealed that cylinder seals and impressions were prevalent at the Southeast Anatolian and Cilician–Amuq sites, areas that interacted with the Mesopotamian cultural sphere during early Early Bronze Age. In the later Early Bronze Age, these artifacts spread to Central and Western Anatolia, facilitated by trade routes known as the Anatolian Trade Network or Caravan Roads. The limited number of cylinder seals and the near absence of their impressions on clay bullae in Western Anatolia indicate that cylinder seals did not support the indigenous stamp seal tradition of the region. Moreover, they were not adopted as bureaucratic tools similar to their use in Mesopotamia. Instead, it is posited that as cylinder seals moved farther from their region of origin, they transitioned into prestige items or simple protective amulets rather than organizational instruments.